2010
DOI: 10.1007/s10344-010-0416-7
|View full text |Cite
|
Sign up to set email alerts
|

Alpine ibex (Capra i. ibex) is not a reservoir for chlamydial infections of domestic ruminants and humans

Abstract: Chlamydophila (C.) abortus is the most common infectious abortigenic agent in small domestic ruminants in Switzerland. In contrast, the knowledge about chlamydiae in wild ruminants is scarce. As interactions between livestock and Alpine ibex (Capra i. ibex) occur on alpine pastures, the question raises if wild ruminants could play a role as carriers of chlamydiae. Thus, we investigated the prevalence of chlamydiae in Alpine ibex in Switzerland. In total, 624 sera, 676 eye swabs, 84 organ samples and 51 faecal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
3
11
0
Order By: Relevance
“…4 The question was raised whether wild ruminants play a role in the transmission of chlamydiosis. In a previous study, a low prevalence of Chlamydiaceae was demonstrated in Alpine ibex (Capra i. ibex) of Switzerland, 16 but the situation in other wild ruminants still remains to be elucidated. Alpine chamois (Rupicapra r. rupicapra) are known to be in contact with domestic sheep and goats on Alpine pastures 21 and could therefore possibly play a role in distribution and transmission of infectious diseases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 The question was raised whether wild ruminants play a role in the transmission of chlamydiosis. In a previous study, a low prevalence of Chlamydiaceae was demonstrated in Alpine ibex (Capra i. ibex) of Switzerland, 16 but the situation in other wild ruminants still remains to be elucidated. Alpine chamois (Rupicapra r. rupicapra) are known to be in contact with domestic sheep and goats on Alpine pastures 21 and could therefore possibly play a role in distribution and transmission of infectious diseases.…”
mentioning
confidence: 99%
“…The DNA extraction was performed using a nucleic acid isolation system, a as previously described, 16 followed by real-time PCR for Chlamydiaceae on a commercial instrument b using the previously described 23S ribosomal RNA gene-based Chlamydiaceae family-specific real-time PCR.…”
mentioning
confidence: 99%
“…In livestock, C. pecorum may result in unapparent subclinical infections or may cause diseases including encephalomyelitis and polyarthritis (Jelocnik et al 2014). Chlamydia pecorum has recently been detected in several previously unrecognized wild hosts including water buffalo (Bubalus bubalis; Greco et al 2008), Alpine ibex (Capra ibex; Holzwarth et al 2011a), chamois (Rupicapra r. Rupicapra; Holzwarth et al 2011b), red deer (Cervus elaphus; Regenscheit et al 2012), and birds (Frutos et al 2012).…”
mentioning
confidence: 99%
“…The initial collection (Table 1) targeted in this study consisted of a previously screened cohort of ocular swabs collected from six hunted ibex (n57; both eyes from one animal; Holzwarth et al 2011a) and a chamois (n51; Holzwarth et al 2011b) and a fecal sample from a hunted red deer (Regenscheit et al 2012). The chamois had corneal lesions and blindness; the other animals had no clinical signs of disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation